2022
DOI: 10.3390/agronomy12123139
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Preventive Activity of Chitosan, Equisetum arvense, Lecithin and Salix Cortex against Plasmopara viticola, the Causal Agent of Downy Mildew in Grapevine

Abstract: Grapevine, a crop of global economic importance, is annually affected by diseases that can compromise the quality and quantity of the harvest, producing large economic losses. Downy mildew caused by Plasmopara viticola (Berk. & M.A. Curtis) Berl. & de Toni is one of the most important diseases in the vineyard. To fight this pathogen, winegrowers often rely on conventional chemical fungicides or copper-based formulations, whose use is determined to be reduced by the European Commission due to their envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…This compound has also been tested for its effect against VWO, showing a 22% reduction in disease severity, 27 as well as against grapevine downy mildew, showing less than a 30% reduction in disease severity. 56 However, in planta experiments revealed a moderate effectiveness of the two chitosan products against VWO because 70.9% and 66.4% of disease progress reduction was observed for chitosan 1 and chitosan 2, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This compound has also been tested for its effect against VWO, showing a 22% reduction in disease severity, 27 as well as against grapevine downy mildew, showing less than a 30% reduction in disease severity. 56 However, in planta experiments revealed a moderate effectiveness of the two chitosan products against VWO because 70.9% and 66.4% of disease progress reduction was observed for chitosan 1 and chitosan 2, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…Andreu et al 55 observed a low effect of willow extract on the mycelial growth of postharvest fungi such as Botrytis allii, Botrytis cinerea, Penicillium expansum, Monilinia laxa and Monilinia fructigena, with inhibition not exceeding 26% for any of these fungi. In addition, Andreu et al 55 and Llamazares-Miguel et al 56 demonstrated that willow extract completely inhibited the germination of Plasmopara viticola spores. Llamazares-Miguel et al 56 also showed that the willow extract reduced downy mildew severity 4), copper phosphite (5), horsetail extract (6), mimosa and oak extract (7), Al ligno.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known to have preventive effects on fungal diseases, attributable to the high percentage of silica [ 60 , 61 ] and antifungal effects linked to its high concentration of flavonoids and phenols [ 62 ]. To date, there are some reports documenting its efficacy in the control of plant pathogens such as Plamopara viticola [ 63 , 64 ], Alternaria solani [ 65 ], Phytophthora infestans , Puccinia triticina [ 66 ] and grapevine trunk pathogens [ 67 ]. In in vitro assays carried out in this work, both Biorend (chitosan) and Equibasic (equisetum) significantly inhibited the growth of C. gloeosporioides at all the tested concentrations, with best results observed at 1% of commercial product.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a careful evaluation of the outcomes of basic substances' employment in the open field is highly necessary. Fortunately, the literature regarding both the approved and potential basic substances is continuously growing, as evidenced from scientific studies and review papers [20][21][22][23][24][25][26][27] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%